Effects Of Standardized Hydroalcoholic Extracts Of Orthosiphon Stamineus On Behaviour Of Gestationally-stressed Postpartum Rats - Othman, Nabilah (2019)
Orthosiphon stamineus (OS) has been traditionally used for many ailments but for psychiatric disorders. Rosmarinic acid (RA) is one of the phenolic compounds contained in OS, and it has been shown to have positive antidepressant-like effect on rats in other studies. The objective of this study is to investigate the effects of ethanolic OS extract on the behaviours of rat dams exposed to gestational stress, which is linked to being a factor of postpartum depressive-like behaviours in rodents. Extraction of OS was carried out using the maceration technique for 48 hours. Through HPTLC, the presence of RA, eupatorin, sinensetin, and TMF were confirmed. The highest percentage of extract yield was from 50% ethanol, while the most concentration of RA obtained was from 95% ethanol. For in vivo study, 50% ethanolic OS extract was chosen to be administered to the rats. Female Sprague Dawley rats were mated and divided into two groups – stressed and non-stressed. The stressed group was subjected to chronic mild stress procedure after mating until the day of parturition, whereas the non-stressed group was left undisturbed. After parturition, the stressed group was further divided into 4 groups – non-treated, amitriptyline-treated 20mg/kg (Ami), OS-treated 100mg/kg (OS100) and OS-treated 200mg/kg (OS200). Treatments were given to the rat dams via oral once daily until the end of the behavioural tests. After weaning of pups, all rat dams were tested for locomotor activity and anxiety-like behaviour in open field test, whereas depression-like behaviour was assessed in forced swim test (all groups n: 7-10)